Aceh Government's Responsibility in Implementing Mandatory Affairs in the Health Insurance Sector - Teuku Rahmat Azhar; Efendi Efendi; Muhammad Insa Ansari (International Journal of Law and Society, 2026)
Based on Law No. 11 of 2006 and Qanun Aceh No. 4 of 2010, the Government of Aceh has special authority in implementing prioritized health services for poor communities as part of its special autonomy. In practice, the Aceh Health Insurance (JKA) program provides health coverage for all Acehnese residents, including underprivileged groups, by covering insurance contributions and several referral and companion costs not fully guaranteed by the national health insurance system. This study aims to analyze the implementation system of JKA, examine the responsibility of the Aceh Government in providing health insurance for its citizens, and evaluate the government’s obligation to pay contributions for poor participants. This research uses an empirical juridical method with a sociological approach and utilizes both primary and secondary data. The results show that several provisions in the Qanun as the legal basis for JKA implementation are not fully aligned with field conditions and the Social Security Administrator Law. In practice, the Aceh Government bears insurance contributions and various referral costs for residents, including poor communities. Although the obligation to pay contributions for the poor has been implemented, funding for referral transportation, companions, and their consumption has not been fully covered, especially for inter-regional advanced healthcare services. Therefore, the Aceh Government needs to revise Article 43 of Qanun Aceh No. 4 of 2010 and evaluate the JKA program to ensure more targeted healthcare financing.